Minoxidil nanocrystal suspension and preparation method thereof
By using non-ionic surfactants such as hydroxypropyl cellulose and pre-shear technology, the particle size and distribution of minoxidil nanocrystal suspension are accurately controlled, and the problems of uneven particle size and poor stability in the prior art are solved, and a small-sized, uniformly dispersed and stable suspension of minoxidil nanocrystal suspension is achieved, which improves the solubility and delivery effect of the drug.
Patent Information
- Application Number
- CN202510194699.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-21
AI Technical Summary
The existing minoxidil nanocrystal suspension has uneven particle size, poor stability, and high content stabilizers affect drug delivery effect and preparation efficiency.
Nonionic surfactants such as hydroxypropyl cellulose are used as stabilizers, combined with pre-shear and ball milling technology, the average particle size and distribution of nanocrystal suspension are accurately controlled to reduce the amount of stabilizer.
The small size, uniform dispersion and stable suspension of the minoxidil nanocrystal suspension is achieved, which improves the solubility and delivery effect of the drug and reduces production costs.
Smart Images

Figure CN119656108A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of pharmaceutical preparations, and particularly relates to a minoxidil nanocrystal suspension and a preparation method thereof. Background Art
[0002] Minoxidil was initially used as an oral drug for the treatment of hypertension. Hair regeneration and systemic hirsutism were found in patients, and it has subsequently become a first-line product for the treatment of male pattern baldness. Minoxidil has extremely poor solubility in water, and a large amount of propylene glycol is often used to improve its solubility and promote transdermal absorption. Although the use of 50% propylene glycol improves the solubility of the active ingredient, it is easy to cause irritation and poor compliance such as dermatitis and dandruff. Chinese patent application CN102349913A high-concentration glycerol-type minoxidil tincture and its preparation method mentioned: When minoxidil is placed in a mixed solvent of water, ethanol and glycerol, no matter how the ratio of the three is adjusted, the minoxidil concentration cannot reach more than 2%. It can be seen that the problem of difficulty in dissolving minoxidil has always been the main problem faced in the preparation process. How to improve the solubility of minoxidil and increase the content of minoxidil in the preparation has also become a focus of subsequent research.
[0003] Drug nano-ization refers to the preparation of drugs into nano-scale particles. For some poorly soluble drugs, nano-ization can significantly increase their surface area to volume ratio, thereby enhancing the dissolution rate and solubility of the drug. However, the content of stabilizers in most nanocrystalline suspensions on the market is relatively large, and even the content of stabilizers is greater than the content of the drug itself. These high-content stabilizers may affect the delivery effect or preparation efficiency of the drug to a certain extent. Taking minoxidil nanocrystalline suspension as an example, Chinese patent application CN116919898A minoxidil nanocrystalline suspension composition, minoxidil nanocrystalline suspension and its preparation method and application discloses the use of wet media grinding, using vitamin E polyethylene glycol succinate as a stabilizer, and the prepared minoxidil nanocrystalline suspension has a particle size of 300 nm, PDI=0.4, and its particle size distribution is not uniform enough. In the characterization test, it can be seen that there are large particles, and the content of stabilizers and adjuvants used in this technology is more than the drug content, which may affect the further use of minoxidil.
[0004] Due to the unique physical and chemical properties of minoxidil, it is very difficult to process it into nano-sized particles and keep it stable. At the same time, due to the characteristics of minoxidil's own application field, the difficulty of preparing minoxidil nanocrystalline suspension is further increased. Therefore, there is an urgent need for a minoxidil nanocrystalline suspension that is small in size, uniformly dispersed, stably suspended, safe to use, and suitable for large-scale industrial production, and a preparation method thereof. Summary of the invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a minoxidil nanocrystalline suspension and a preparation method thereof, which can realize the precise control of the small average particle size and narrow distribution of the minoxidil nanocrystalline suspension, solve the problem that the minoxidil nanocrystalline suspension is easy to aggregate and precipitate, and has high storage stability. The method of the present invention is low in cost and easy to industrialize.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solution: a method for preparing a minoxidil nanocrystal suspension, comprising the following steps: S1. Add a stabilizer to water under stirring conditions, and stir evenly to obtain a stabilizer mixed solution; the stabilizer includes a nonionic surfactant; S2, adding minoxidil to the stabilizer mixture to obtain a minoxidil mixture, stirring the minoxidil mixture to room temperature, and then placing it in a high-speed shearing machine for pre-shearing until it is uniformly mixed to obtain a coarse suspension; S3, grinding the coarse suspension, and filtering after grinding to obtain a minoxidil nanocrystal suspension.
[0007] The present invention combines a method of pre-shearing after mixing a non-ionic surfactant as a stabilizer with minoxidil without adding other redundant components, thereby achieving precise control of a small average particle size and a narrow distribution of a nanocrystalline suspension.
[0008] Furthermore, the nonionic surfactant includes hydroxypropyl cellulose.
[0009] Furthermore, the nonionic surfactant also includes one or more of hydroxyethyl cellulose, sodium hydroxymethyl cellulose, polyvinyl alcohol, Tween, and polyvinyl pyrrolidone.
[0010] Furthermore, the stabilizer also includes an ionic surfactant.
[0011] Furthermore, the ionic surfactant is selected from one or more of stearic acid, sodium cholate, sodium deoxycholate, hexadecyltrimethylammonium bromide, and lecithin.
[0012] The minoxidil nanocrystalline suspension of the present invention uses a nonionic polymer as a stabilizer to prepare a stable nanocrystalline suspension. When the stabilizer is hydroxypropyl cellulose (HPC), and in combination with various parameters in the grinding process, the dissolution conditions of HPC and the degree of wetting and bonding between HPC and minoxidil are accurately controlled, the particle size and monodispersity coefficient of the prepared nanocrystalline suspension can be reduced, and the stabilizer of the nanocrystalline suspension, including the particle size stability and the suspension stability of the suspension, can be improved, thereby preparing a small-sized, uniformly dispersed, and stably suspended minoxidil nanocrystalline suspension. Under this condition, the drug particles can be effectively wetted, and sufficient steric hindrance and / or electrostatic barrier can be provided for the drug particles to prevent aggregation over time.
[0013] Furthermore, the mass percentage of the stabilizer in the stabilizer mixture is 0.1-1.0%.
[0014] Furthermore, the stabilizer is a compound of hydroxypropyl cellulose (HPC), polyvinyl pyrrolidone (PVP) and sodium cholate in a mass ratio of (0.1-1.0): (0.2-0.6): (0.1-0.7).
[0015] The minoxidil nanocrystal suspension prepared by using a nonionic polymer or a charged ionic surfactant alone has an unstable tendency in terms of particle size, monodispersity coefficient, or suspension stabilizer (with or without precipitation), and the particles aggregate, that is, the particle size and PDI become larger or the suspension is unstable and precipitates. In order to further obtain a smaller particle size and stable minoxidil nanocrystal suspension, the present invention can further improve the particle size and stability of the minoxidil nanocrystal suspension stored at different temperatures by using a specific ratio of hydroxypropyl cellulose (HPC), PVP and sodium cholate. The compounding of different surfactants has a 1+1>2 effect. Analysis shows that when HPC or other stabilizers are used alone, the steric hindrance or electrostatic repulsion provided by them is not enough to stabilize the minoxidil nanocrystal suspension. At the same time, because minoxidil is a highly hydrophobic drug, under the hydrophobic effect, there is a balance between the repulsive potential energy and the attractive potential energy of minoxidil particles. At this time, the addition of a stabilizer must be able to overcome the van der Waals force or the attractive interaction between particles in order to disperse the particles, which means that the repulsive interaction provided by the stabilizer in the system must be greater than the attractive interaction between the drugs. The compounded stabilizer can provide steric hindrance and electrostatic repulsion to the drug at the same time, thereby obtaining a smaller particle size and more stable minoxidil nanocrystal suspension, while improving storage stability.
[0016] Furthermore, the mass percentage of minoxidil in the mixed solution in step S2 is 0.5-15%.
[0017] Furthermore, the pre-shearing conditions in step S2 are: shearing speed is 3500-7000 rpm / min, shearing time is 5-20 min, and shearing temperature is 20-35°C.
[0018] The present invention can improve the particle size and dispersion uniformity of the minoxidil nanocrystalline suspension by mixing and dissolving the stabilizer and minoxidil, pre-shearing the mixture through a high-speed shearing machine, and then grinding the mixture. It is found in the test process that under specific pre-shearing conditions, the pre-shearing method can produce a synergistic effect with the stabilizer to prepare a minoxidil nanocrystalline suspension with good storage stability under different temperature conditions.
[0019] Furthermore, the stirring speed in step S1 and step S2 is 200-1000 rpm / min.
[0020] Further, the coarse suspension is mixed with zirconium oxide beads for grinding; the volume ratio of the coarse suspension to the zirconium oxide beads is 1:0.5-5, and the diameter of the zirconium oxide beads is 0.2-1.0 mm.
[0021] Furthermore, the grinding parameters in step S3 are: rotation speed 200-2000 rpm, grinding temperature 4-40° C., and grinding time 0.5-4 h.
[0022] Further, filtering is performed under a standard sieve, and the standard sieve specification is 50-100 mesh.
[0023] The second aspect of the present invention provides a minoxidil nanocrystalline suspension prepared by the above-mentioned preparation method.
[0024] Furthermore, the minoxidil nanocrystal suspension is used to prepare medicines for treating androgenic alopecia, alopecia areata, chemotherapy-induced alopecia, and refractory hypertension.
[0025] A freeze-drying protective agent is added to the minoxidil nanocrystal suspension prepared by the invention, and after being completely pre-frozen, the suspension is placed in a vacuum freeze dryer and vacuum dried overnight to obtain minoxidil nanocrystal freeze-dried powder.
[0026] The freeze-drying protective agent is selected from at least one of trehalose, mannitol, sucrose, glucose, lactose, sorbitol and fructose.
[0027] The mass percentage of the freeze-dried powder protective agent in the minoxidil nanocrystal suspension is 0.05-5.0%.
[0028] The pre-freezing conditions are liquid nitrogen, -80°C or cold trap for complete pre-freezing for 0.5-4h.
[0029] Compared with the prior art, the present invention has achieved beneficial technical effects: 1. This invention prepares a small-sized, uniformly dispersed, and stably suspended minoxidil nanocrystal suspension, provides a wet medium ball milling method, and can nanosize the drug without using a carrier or an organic solvent, and avoids the problem of high-concentration stabilizers on the subsequent formulation and safety. The present invention uses a specific stabilizer prescription ratio and the synergistic effect of pre-shearing process adjustment and operation parameter optimization, and uses a very small amount of stabilizer (<1.0 wt.%) to fully wet the drug particles and stabilize the nanocrystal suspension, thereby realizing the preparation of small-sized minoxidil nanocrystals; 2. The present invention provides a method for preparing a minoxidil nanocrystal suspension, which uses a stable wet medium ball milling technology to greatly improve the energy utilization efficiency. The preparation of minoxidil nanocrystals can be completed only by ball milling and a small amount of stabilizer compounding; 3. In the process of converting the preparation of minoxidil nanocrystal suspension from small-scale trials to large-scale production, maintaining consistency in product quality is an important challenge. When scaling up production, new problems may arise, such as uneven mixing, changes in particle morphology, etc. Traditional ultrasound is difficult to scale up, and the centrifugation step is long. The present invention uses the synergistic effect of pre-shearing and stabilizers, and does not require ultrasound and centrifugation, so that the obtained particle size is smaller and more uniform, without double peaks. The preparation conditions of the present invention are mild, and the crystal structure of minoxidil nanocrystals is not changed. It can be applied to large-scale production and has extremely high economic value and market prospects; 4. The minoxidil nanocrystal suspension prepared by the present invention has excellent long-term storage stability under different temperature conditions through the synergistic effect of the stabilizer and the pre-shearing treatment; 5. The affinity between HPC and minoxidil in the present invention is the best. By compounding HPC with other nonionic polymers and charged ionic surfactants, better steric hindrance and electrostatic repulsion can be provided for the nanocrystalline suspension. At the same time, the stability of the compounding can make the stability and release of the minoxidil nanocrystalline suspension better; 6. The present invention adjusts the type and amount of the stabilizer, utilizes nonionic polymers and charged ionic surfactants to simultaneously provide steric hindrance and electrostatic repulsion to reduce the particle size of the drug and stabilize the nanocrystalline suspension, and utilizes a high-speed pre-shearing method before ball milling to fully infiltrate the drug particles with the stabilizer, thereby nano-sizing the drug without using a carrier or an organic solvent, thereby improving the water solubility of the drug and avoiding the influence of high-concentration stabilizers on subsequent formulations and the drug itself. By optimizing the operating parameters of the ball mill and the content of the stabilizer in the suspension, the preparation of a minoxidil nanocrystalline suspension with small size, uniform dispersion, stable suspension, good solubility, safety and energy saving is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1The present invention is a schematic flow diagram of the method for preparing the minoxidil nanocrystal suspension; Figure 2 A schematic diagram of the minoxidil nanocrystal suspension prepared in Example 3; Figure 3 This is a schematic diagram of the dynamic light scattering particle size distribution of Example 3; Figure 4 This is a schematic diagram of the dynamic light scattering particle size distribution of Comparative Example 1; Figure 5 Schematic diagram of Zeta potential of Example 3; Figure 6 This is a schematic diagram of the SEM scan of minoxidil raw material; Figure 7 Schematic diagram of SEM scanning of the minoxidil nanocrystal suspension of Example 3; Figure 8 The XRD patterns of the minoxidil nanocrystal suspension and the minoxidil bulk drug of Example 3; Fig. 9 FTIR spectra of the minoxidil nanocrystal suspension and the minoxidil bulk drug of Example 3; Fig.10 The UV-Vis scanning spectra of the minoxidil nanocrystal suspension and the minoxidil bulk drug of Example 3; Fig.11 The in vitro release curves of the minoxidil nanocrystal suspension and the minoxidil bulk drug of Example 3; Fig.12 The in vitro release curves of the minoxidil nanocrystal suspensions of Example 3, Example 6, Comparative Example 1, and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0031] In order to allow those skilled in the art to better understand this solution, the solution is further described in detail below in conjunction with specific examples. The process methods used in the examples are all conventional methods unless otherwise specified; the materials used are all commercially available unless otherwise specified.
[0032] Examples 1-4 Effect of different HPC dosages on the preparation of minoxidil nanocrystalline suspension.
[0033] like Figure 1 As shown, this embodiment provides a minoxidil nanocrystal suspension, and the preparation method thereof comprises the following steps: S1. Slowly add hydroxypropyl cellulose (addition amount see Table 1) into 100 mL of water, stir until completely dissolved, then add 0.25 g polyvinyl pyrrolidone (PVP-K30, average molecular weight 58000) and 0.25 g sodium cholate, stir at 500 rpm / min until completely dissolved, and use as a stabilizer mixture for later use; S2, add 10g minoxidil per 100mL of the stabilizer mixture to obtain a minoxidil mixture, stir at a speed of 1000rpm for 10min, and after the minoxidil mixture returns to room temperature, put it on a high-speed shearing machine for shearing at a temperature of 25°C and a speed of 5000rpm for 10min to obtain a coarse suspension; S3. Use a centrifugal ball mill to transfer the coarse suspension to a grinding jar, and set the grinding parameters: grinding beads (zirconia beads) with a diameter of 0.4-0.5 mm, a rotation speed of 450 rpm, and a ratio of coarse suspension to grinding beads of 1:1.5 (volume ratio). After grinding for 3 hours, pass through a 100-mesh standard sieve to obtain a minoxidil nanocrystalline suspension.
[0034] The steps of preparing minoxidil nanocrystal suspension into freeze-dried powder are as follows: add 2 g of mannitol (lyophilization protective agent) to every 100 mL of suspension, pre-freeze completely at -80°C, and place in a vacuum freeze dryer for vacuum drying overnight to obtain minoxidil nanocrystal freeze-dried powder.
[0035] According to the above S1-S3 operations, the minoxidil nanocrystal suspension was subjected to dynamic light scattering (DLS) test, and the results are recorded in Table 1.
[0036]
[0037] From the data in Table 1, it can be seen that fixing the content of other stabilizers and changing the dosage in the HPC system has a certain effect on the particle size of the suspension, which is manifested in that the particle size first decreases and then increases with the addition amount of HPC. Figure 2 Schematic diagram of the minoxidil nanocrystal suspension prepared in Example 3.
[0038] Example 5 The difference between this embodiment and embodiment 3 is that PVP is not added in step S1, and 0.65g HPC and 0.25g sodium cholate are compounded to prepare a stabilizer mixture. Then, the minoxidil nanocrystal suspension is prepared in the same manner as in embodiment 3, and the results are characterized.
[0039] Example 6 The difference between this embodiment and embodiment 3 is that only 0.9 g of HPC is added in step S1 to prepare a stabilizer mixed solution. Then, the minoxidil nanocrystal suspension is prepared in the same manner as in embodiment 3, and the results are characterized.
[0040] Example 7 The difference between this embodiment and embodiment 3 is that in step S1, only 0.9 g of polyvinyl pyrrolidone (PVP) is used as a stabilizer to prepare a stabilizer mixed solution. Then, the minoxidil nanocrystal suspension is prepared in the same manner as in embodiment 3, and the results are characterized.
[0041] Example 8 The difference between this embodiment and embodiment 3 is that in step S1, only 0.9 g of sodium cholate is used as a stabilizer to prepare a stabilizer mixture. Then, the minoxidil nanocrystal suspension is prepared in the same manner as in embodiment 3, and the results are characterized.
[0042] Example 9 The difference between this embodiment and embodiment 3 is that in step S1, only 0.9 g of sodium hydroxymethylcellulose is used as a stabilizer to prepare a stabilizer mixed solution. Then, the minoxidil nanocrystal suspension is prepared in the same manner as in embodiment 3, and the results are characterized.
[0043] Comparative Example 1 The difference between this comparative example and Example 3 is that in step S1, only 0.9 g of vitamin E polyethylene glycol succinate (ViE-TPGS) is used as a stabilizer, and then the minoxidil nanocrystal suspension is prepared according to the subsequent steps of Example 3, and the results are characterized.
[0044] Comparative Example 2 The difference between this comparative example and Example 3 is that in step S1, only 0.9 g of hydroxypropyl methylcellulose (HPMC) is used as a stabilizer, and then the minoxidil nanocrystal suspension is prepared in the same manner as in Example 3, and the results are characterized.
[0045] Comparative Example 3 The difference between this comparative example and Example 3 is that in step S1, only 0.9 g of Poloxamer 188 was used as the stabilizer, and then the minoxidil nanocrystal suspension was prepared in the same manner as in Example 3, and the results were characterized.
[0046] Comparative Example 4 The difference between this comparative example and Example 3 is that in step S1, only 0.9 g of sodium dodecyl sulfate (SDS) is used as a stabilizer, and then the minoxidil nanocrystal suspension is prepared in the same manner as in Example 1, and the results are characterized.
[0047] Examples 10-14 and Comparative Examples 5-8 The difference from Example 3 is that the shearing conditions are different. In step S2, no pre-shearing is performed or the shearing speed is adjusted to 3500 rpm, 5000 rpm, 7000 rpm, 9000 rpm or the shearing time is adjusted to 5 min, 10 min, 20 min or the shearing temperature is increased to 25 ° C, 35 ° C, 50 ° C for direct ball milling to prepare minoxidil nanocrystalline suspension, and the results are characterized. See Table 3 for details.
[0048] Performance Testing 1. Evaluation of the effect of different types of stabilizers on the suspension properties of minoxidil nanocrystals The suspension states of the suspensions of Examples 6-9 and Comparative Examples 1-4 after standing for 12 hours were detected and recorded respectively, and the results are recorded in Table 2.
[0049]
[0050] From the data in Table 2, it can be seen that under the same conditions, the stability of the minoxidil nanocrystal suspension prepared by using a single stabilizer, hydroxypropyl cellulose, is the highest, with only a small amount of precipitation after standing for 12 hours; followed by polyvinyl pyrrolidone, sodium cholate and sodium hydroxymethyl cellulose, which began to have a large amount of precipitation after standing for 12 hours; while vitamin E polyethylene glycol succinate, hydroxypropyl methylcellulose, poloxamer 188, sodium dodecyl sulfate, etc. have the worst stability, and all precipitate after standing for 12 hours. The scientific name of minoxidil is: 6-(1-piperidinyl)-2,4-pyrimidinediamine-3-oxide, which contains two amino structures and a piperidine group. This molecule can provide three unique hydrogen bond donors and three hydrogen bond acceptors. It is worth noting that both HPC and sodium cholate contain rich ether bonds or hydroxyl groups, and also have hydrogen bond donor and acceptor functions. They can form a surface active layer with both steric hindrance and electrostatic barrier effects on the surface of minoxidil nanocrystals through intermolecular hydrogen bonding, thereby reducing the aggregation of nanocrystals and improving stability.
[0051] 2. Evaluation of the effect of HPC shear conditions on minoxidil nanocrystal suspension The D90 of Examples 6, 10-14 and Comparative Examples 5-8 and the suspension state after standing for 12 hours were detected and recorded respectively, and the results are recorded in Table 3:
[0052] From the data in Table 3, it can be seen that the pre-shearing step after the HPC and minoxidil are mixed before ball milling has a great influence on the particle size and its stability, that is, under the same conditions, if the HPC is not pre-sheared with the mixed solution of minoxidil before ball milling, there are obvious large particles in the prepared nanocrystalline suspension, and D90>4000nm. This may be because the pre-shearing method with mild conditions can make the stabilizer combined with minoxidil in advance, avoiding the high-energy shear force generated by the machine operation during the ball milling process and the force generated when the medium collides with the drug to destroy the structure and affect its stability. At the same time, the comparison of Example 6 and Comparative Example 5 can illustrate the influence of the pre-shearing of HPC on the whole system. It is shown that the present invention can only prepare a nanocrystalline suspension with good storage stability under specific stabilizers and specific pre-shearing conditions.
[0053] Different HPC treatment conditions also have a certain influence on the particle size and stability of the nanocrystalline suspension. From the data in Table 2, it can be seen that when the shear speed exceeds 9000rpm or the shear temperature is greater than 50℃, the particle size of the nanocrystalline suspension will rise sharply and the suspension will be unstable and a large amount of precipitation will occur, while the shear time of 5-20min has little effect on the results; when the HPC shear conditions are at a shear speed of 3500-7000rpm, a shear temperature below 35℃ and a shear time of 5-20min, the particle size and stabilizer of the minoxidil nanocrystalline suspension with HPC as a stabilizer are optimal.
[0054] The method for treating HPC in Example 6 of the present invention is characterized in that HPC is mildly treated in advance, that is, the mixture of HPC and minoxidil is pre-sheared before ball milling, so that the HPC is fully infiltrated and bonded to the minoxidil particles, thereby preventing the free HPC from being destroyed by the high-energy shear force during the ball milling process, thereby affecting its own performance. At the same time, pre-bonding to the drug particles can also provide sufficient steric hindrance and / or electrostatic barrier for the minoxidil particles to prevent aggregation over time.
[0055] 3. Evaluate the effect of different types of stabilizers on the particle size and monodispersity of minoxidil nanocrystal suspension The particle sizes and monodispersity coefficients of Examples 6-9 and Comparative Examples 1-4 were measured and recorded when prepared and 14 days later, and the results are recorded in Table 4:
[0056] From the data in Table 4, it can be seen that under the same conditions, the average particle size of the minoxidil nanocrystalline suspension prepared by using a single stabilizer such as hydroxypropyl cellulose, polyvinyl pyrrolidone, sodium cholate, and sodium hydroxypropyl cellulose has a range of 200-400nm, a PDI of 0.2-0.3, a small deviation between parallel samples, and high stability; the particle size is small and the dispersion is uniform; among them, hydroxypropyl cellulose and polyvinyl pyrrolidone are the most stable, and the particle size and PDI have almost no change after being placed at room temperature for half a month; while the particle size or PDI of sodium cholate, sodium hydroxypropyl cellulose, etc. have a tendency to increase to varying degrees and the deviation between parallel samples is huge, and the reproducibility of batch preparation is low.
[0057] From the data in Table 3 and Table 4, it can be seen that the overall stability and particle size dispersion of HPC are the best.
[0058] 4. Evaluation of the effect of HPC compounded ionic surfactants on the suspension of minoxidil nanocrystals The suspension states of the suspensions of Examples 3 and 5-6 after standing at room temperature for 12 hours were detected and recorded respectively, and the results are recorded in Table 5:
[0059] From the results in Table 5, it can be seen that after the non-ionic polymer HPC is compounded with other ionic surfactants, the stability of the minoxidil nanocrystalline suspension is improved, and no sedimentation occurs after standing. This shows that compounding HPC with other ionic surfactants can improve the stability of the minoxidil nanocrystalline suspension.
[0060] 5. Evaluation of the effect of HPC compounded ionic surfactants on the particle size and monodispersity of minoxidil nanocrystal suspension The changes in particle size and monodispersity coefficient of Example 3 and Examples 5-6 within 30 days after preparation were detected and recorded respectively, and the results are recorded in Table 6:
[0061] From the data in Table 6, it can be seen that after HPC is compounded with ionic surfactants, its particle size or monodispersity coefficient becomes smaller to varying degrees. Combined with the data in Table 5, it can be seen that HPC compounded with ionic surfactants can provide smaller particle size and higher suspension stability than HPC or ionic surfactants alone, that is, the simultaneous presence of steric hindrance and electrostatic repulsion in the suspension system can achieve better stability and reduce the particle size and monodispersity coefficient.
[0062] The Zeta potential of the minoxidil nanocrystal suspension prepared in Example 3 was detected. Figure 3 , Figure 5 As shown, Figure 4 By comparison, it can be seen that the absolute value of the Zeta potential of Example 3 is high (Zeta potential is -33.54), indicating that the suspension is a stable system.
[0063] The SEM of the minoxidil nanocrystal suspension and the minoxidil bulk drug prepared in Test Example 3 is as follows: Figure 6-7 As shown, the particle size of Example 3 is much smaller than that of the raw material and is uniform, indicating that the minoxidil nanocrystalline suspension obtained in Example 3 is a nanoparticle with a small and uniform particle size.
[0064] The XRD of the minoxidil nanocrystalline freeze-dried powder and the minoxidil bulk drug prepared in Example 3 was tested (the test angle 2θ was in the range of 5-80°, the test step size was 0.04, and the integration time was 0.5 s). Figure 8 As shown, the crystal structure of minoxidil nanocrystals is similar to that of minoxidil bulk drug, indicating that the structure of minoxidil nanocrystals obtained in Example 3 has not changed during the preparation process.
[0065] The FTIR (scanning wavelength 400-4000 cm-1) of the minoxidil nanocrystalline freeze-dried powder and the minoxidil bulk drug prepared in Example 3 was tested. Fig. 9As shown, the spectrum of minoxidil nanocrystals is basically consistent with the spectrum of the raw material drug, indicating that the crystal structure of the minoxidil nanocrystals obtained in Example 3 has not changed during the preparation process. The technical solution of the present invention can avoid the problem that ball milling in the preparation of minoxidil suspension in the prior art may cause crystal transformation, which may have an adverse effect on the performance and efficacy of the drug.
[0066] Scan the absorption wavelength of the minoxidil nanocrystal suspension prepared in Example 3 and the minoxidil bulk drug under ultraviolet light (scanning wavelength 200-400nm), as shown in Fig.10 As shown, both the minoxidil nanocrystal suspension and the minoxidil bulk drug have absorption peaks at 229 nm, 262 nm, and 287 nm, wherein 229 nm is the maximum absorption wavelength, indicating that the structure of the minoxidil nanocrystals obtained in Example 3 has not changed during the preparation process.
[0067] 6. The nanocrystal suspensions prepared in Examples 3, 5, 6 and Comparative Example 5 were placed at 4°C, 25°C (room temperature) and 40°C for 9 months and then tested. The results are shown in Table 7.
[0068]
[0069] It can be seen from Table 7 that the minoxidil nanocrystalline suspensions prepared in Examples 3, 5, and 6 have better stability in particle size, PDI, and D90nm after storage at different temperatures, which are significantly better than those in Comparative Example 5, among which Example 3 has a better overall effect. This indicates that the compounded stabilizer and pre-shearing treatment have an important influence on the stability of the minoxidil nanocrystalline suspension at different temperatures.
[0070] 7. In vitro release test The in vitro release of the minoxidil nanocrystalline suspension and / or the minoxidil API prepared in Example 3, Example 6 and Comparative Examples 1-2 was tested. The specific operation was as follows: the minoxidil nanocrystalline suspension and the minoxidil API solution of the same concentration in Example 3, Example 6 and Comparative Examples 1-2 were placed in a 30KDa dialysis bag, and then placed in 500mL of PBS7.4 with a volume of 1X coarse suspension and zirconium oxide beads, stirred in a water bath at 37°C, and 5mL of the dissolution medium (PBS) was taken for detection (UV, 230nm) at 10min, 20min, 40min, 1h, 2h, 4h, 6h, 8h, and 22, respectively, and a new equal volume of PBS was taken to make up. The results are shown in FIG. Fig.11 As shown, the in vitro release of minoxidil API is not as good as that of minoxidil nanocrystals. The release of minoxidil nanocrystals within 4 hours is about 90%, while that of API is only about 50%, indicating that the minoxidil nanocrystal suspension prepared in Example 3 has better release and transdermal effect than minoxidil API. Figure 11-12As shown, the release pattern of suspensions with different particle sizes in the dissolution medium of PBS7.4 is that the smaller the particle size, the faster the release rate, indicating that the smaller the particle size, the better the penetration-promoting effect of the minoxidil nanocrystal suspension. The present invention uses the synergistic effect of the compounded stabilizer and pre-shearing to make the minoxidil nanocrystal have better release effect and transdermal effect.
[0071] The above are only embodiments of the present application. The protection scope of the present application is not limited by these specific embodiments, but is determined by the claims of the present application. For those skilled in the art, the scope of protection of the present invention should be replacements and modifications that do not deviate from the present invention and are covered by the rights of this patent application.
Claims
1. A method for preparing a minoxidil nanocrystal suspension, characterized in that: The following steps are involved: S1. Add a stabilizer to water under stirring conditions, and stir evenly to obtain a stabilizer mixed solution; the stabilizer includes a nonionic surfactant; S2, adding minoxidil to the stabilizer mixture to obtain a minoxidil mixture, stirring the minoxidil mixture to room temperature, and then placing it in a high-speed shearing machine for pre-shearing until it is uniformly mixed to obtain a coarse suspension; S3, grinding the coarse suspension, and filtering after grinding to obtain a minoxidil nanocrystal suspension.
2. The method for preparing a minoxidil nanocrystal suspension according to claim 1, wherein The nonionic surfactant includes hydroxypropyl cellulose.
3. The method for preparing the minoxidil nanocrystal suspension according to claim 2, wherein: The nonionic surfactant further comprises one or more of hydroxyethyl cellulose, sodium hydroxymethyl cellulose and polyvinyl pyrrolidone.
4. The method for preparing the minoxidil nanocrystal suspension according to claim 3, wherein: The stabilizer also includes ionic surfactants.
5. The method for preparing the minoxidil nanocrystal suspension according to claim 4, characterized in that: The ionic surfactant is selected from sodium cholate.
6. The method for preparing the minoxidil nanocrystal suspension according to claim 5, characterized in that: The stabilizer is a compound of hydroxypropyl cellulose, polyvinyl pyrrolidone and sodium cholate in a mass ratio of (0.1-1.0):(0.2-0.6):(0.1-0.7).
7. The method for preparing the minoxidil nanocrystal suspension according to claim 1, characterized in that: The mass percentage of the stabilizer in the stabilizer mixed solution in step S1 is 0.1-1.0%; the mass percentage of minoxidil in the mixed solution in step S2 is 0.5-15%.
8. The method for preparing the minoxidil nanocrystal suspension according to claim 1, characterized in that: The pre-shearing conditions in step S2 are: shearing speed of 3500-7000 rpm / min, shearing time of 5-20 min, and shearing temperature of 20-35°C.
9. A minoxidil nanocrystal suspension prepared by the preparation method according to any one of claims 1 to 8.
10. The minoxidil nanocrystal suspension according to claim 9, characterized in that: Minoxidil nanocrystal suspension is used to prepare drugs for treating androgenic alopecia, alopecia areata, chemotherapy-induced hair loss, and refractory hypertension.
Citation Information
Patent Citations
High concentration glycerol-type minoxidil tincture and preparation method thereof
CN102349913A
A process for making particles for delivery of drug nanoparticles
CN102164582A
Apremilast nanocrystalline composition and preparation method thereof
CN114432242A
Minoxidil nanocrystal suspension composition, minoxidil nanocrystal suspension as well as preparation method and application of minoxidil nanocrystal suspension
CN116919898A
Polymorphic crystalline forms of celecoxib
US20040087640A1